Autapses enhance bursting and coincidence detection in neocortical pyramidal cells - Luping Yin (Nature Portfolio, 2018)
While autapses are synapses made by a neuron onto itself, its functional significance in pyramidal cells are not clear. Here, the authors show that in the mammalian neocortex, autapses of pyramidal cells can enhance burst firing and coincidence detection from other inputs.